Lactoferrin inhibits aflatoxin B1- and aflatoxin M1-induced cytotoxicity and DNA damage in Caco-2, HEK, Hep-G2, and SK-N-SH cells. (August 2018) - Zheng, Nan; Zhang, Huan; Li, Songli; Wang, Jiaqi; Liu, Jia; Ren, Hui; Gao, Yanan
Abstract: Aflatoxins, including aflatoxin B1 (AFB1 ) and M1 (AFM1 ), are natural potent carcinogens produced by Aspergillus spp. These compounds, which can often be detected in dairy foods, can cause diseases in human beings. However, the molecular mechanisms involved in cytotoxicity, as well as methods for intervention, remain largely unexplored. For example, it is unclear whether lactoferrin (LF), a major antioxidant in milk, can inhibit the cytotoxicity of AFB1 and AFM1 . In this study, we assessed AFB1 - and AFM1 -induced cell toxicity by measuring cell viability, membrane permeability, and genotoxicity, and then investigated the ability of LF to protect cells against AFB1 and AFM1 . In Caco-2, HEK, Hep-G2, and SK-N-SH cells, 4 μg/mL AFB1 or AFM1 significantly inhibited cell growth, increased the level of lactate dehydrogenase, induced genetic damage, and increased the levels of signal-regulated kinase (ERK1/2) and c-Jun N-terminal kinase (JNK) (p < 0.05). AFB1 was more genotoxic than AFM1 in all four cell lines, especially in Hep-G2. In Caco-2, Hep-G2, and SK-N-SH, incubation of AF-treated cells with 1000 μg/mL LF significantly decreased cytotoxicity, oxidation level, DNA damage, and levels of ERK1/2 and JNK (p < 0.05). Our data demonstrate that AFB1 or AFM1 induced cytotoxicity and DNA damage in these four cell lines, and that LF alleviated toxicity by decreasing oxidative stress mediated by mitogen-activated protein kinase pathways. Highlights: The cytotoxicity of aflatoxin B1 and aflatoxin M1 was compared on Caco-2, HEK, Hep-G2, and SK-N-SH cells. Lactoferrin could inhibit the cytotoxicity of aflatoxin B1 and aflatoxin M1. The mechanism relies on signal-regulated kinase and c-Jun N-terminal kinase MAPK pathways.